Early Administration of Remdesivir and Intensive Care Unit Admission in Hospitalized Pregnant Individuals With Coronavirus Disease 2019 (COVID-19). Issue 4 (4th April 2022) - Eid, Joe; Abdelwahab, Mahmoud; Colburn, Nora; Day, Shandra; Cackovic, Michael; Rood, Kara M.; Costantine, Maged M.
Abstract : Early administration of remdesivir is associated with decreased risk of admission to the intensive care unit and decreased length of hospitalization in pregnant individuals hospitalized with coronavirus disease 2019 (COVID-19). Abstract : Remdesivir has been shown to shorten the time to recovery in hospitalized patients with coronavirus disease 2019 (COVID-19). Data on its use in pregnancy are limited. In this single-center retrospective cohort study, our objective was to determine whether early remdesivir use in pregnant individuals is associated with decreased risk of admission to the intensive care unit (ICU). Forty-one pregnant patients were included in this study, and outcomes were compared between those who received remdesivir less than 7 days (early group) and 7 or more days (late group) from onset of patient-reported symptoms. Early remdesivir administration was associated with improved clinical outcomes, including lower rates of ICU admission, decreased length of hospitalization, and decreased progression to critical disease in pregnant individuals hospitalized with COVID-19.